2019
DOI: 10.3390/medicina55050140
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Data on Pollen Monitoring, Distribution and Health Impact of Allergenic Plants in Bucharest and the Southeastern Region of Romania

Abstract: Background and objectives: Respiratory allergies induced by allergenic pollen represent an important public health problem with increasing prevalence and severity in Europe. Romania has no aerobiology network and pollen measurements have been done for about ten years in the west region only. Materials and Methods: We established the first pollen monitoring center in the capital of Bucharest in 2013, based on collaboration with the Réseau National de Surveillance Aérobiologique (RNSA) from France. The aim of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
3
19
1
Order By: Relevance
“…Referring to the risk factors for allergy due to Ambrosia pollen, our study found a significant environmental exposure to the invasive plant, which was declared by almost all patients included in the study group and was also confirmed by our pollen monitoring data 14,15 , while history of atopy was found in only 11.95% of cases. Data from the literature pointed out that the time between exposure to a new allergen in an area until the appearance of allergic sensitization is about 10-15 years 28 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Referring to the risk factors for allergy due to Ambrosia pollen, our study found a significant environmental exposure to the invasive plant, which was declared by almost all patients included in the study group and was also confirmed by our pollen monitoring data 14,15 , while history of atopy was found in only 11.95% of cases. Data from the literature pointed out that the time between exposure to a new allergen in an area until the appearance of allergic sensitization is about 10-15 years 28 .…”
Section: Discussionsupporting
confidence: 81%
“…Our data showed significant amount of Ambrosia pollen in Bucharest, with maximum values during early September, when the plant reaches the peak of flourishing and releases high amount of pollen in the atmosphere 14 . Since 2010 we also performed medical education and public activities dedicated to prevention and early diagnosis of allergies due to Ambrosia pollen and we encouraged allergic patients to associate and be involved in coordinated media campaign 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Allergy to ragweed usually manifests clinically as allergic rhinitis or conjunctivitis, sometimes with associated asthma symptoms [10]. Despite this increasing health problem, there are few studies that have analyzed the impact of ragweed sensitization on the clinical manifestations of allergy, especially in Romania [4,11,12]. Most of the studies focused on determining the pollen level in the air and its correlation with the severity of manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…The period of tree pollination lasts from February to May. The measurement of air pollen concentration is important for monitoring allergenic plant distribution and yearly variations [10]. The importance of allergen pollen measurement is reflected in the timely application of allergen immunotherapy.…”
Section: Introductionmentioning
confidence: 99%